2012
DOI: 10.1155/2012/235234
|View full text |Cite
|
Sign up to set email alerts
|

Association between Urinary N-Acetyl-Beta-D-Glucosaminidase and Microalbuminuria in Diabetic Black Africans

Abstract: Diabetes mellitus is the commonest cause of ESRD worldwide and third most common cause in Nigeria. Recent reports from Nigeria indicate the prevalence of diabetic nephropathy as an aetiology of ESRD is increasing necessitating early diagnosis of diabetic nephropathy. We measured the urinary excretion of N-acetyl-beta-D-glucosaminidase (NAG), NAG/creatinine ratio, urinary protein-creatinine ratio and calculated eGFR in 30 recently diagnosed nonhypertensive diabetics and 67 controls. The age and sex distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
5
4
0
1
Order By: Relevance
“…We found that urinary NAG levels were significantly increased in patients with microalbuminuria compared to those with normoalbuminuria, thus corroborating previous studies performed in type 2 diabetic patients (8)(9)(10). We also observed a significant positive correlation between urinary NAG excretion and ACR which is consis- tent with the data reported by other studies in patients with T2DM (14) as well as in type 1 diabetic patients (15). These findings suggest that tubular dysfunction, evidenced by an increase in urinary NAG excretion, is already present in the microalbuminuria stage of DN in T2DM and that it becomes exacerbated with the degree of albuminuria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that urinary NAG levels were significantly increased in patients with microalbuminuria compared to those with normoalbuminuria, thus corroborating previous studies performed in type 2 diabetic patients (8)(9)(10). We also observed a significant positive correlation between urinary NAG excretion and ACR which is consis- tent with the data reported by other studies in patients with T2DM (14) as well as in type 1 diabetic patients (15). These findings suggest that tubular dysfunction, evidenced by an increase in urinary NAG excretion, is already present in the microalbuminuria stage of DN in T2DM and that it becomes exacerbated with the degree of albuminuria.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of correlation between urinary NAG excretion and glycemic state are consistent with those results reported by other authors in type 2 diabetic patients (9,14). However, data from the literature referred to T2DM are controversial (10,17), while in type 1 diabetic patients such a relation is more clearly evidenced (15).…”
Section: Discussionsupporting
confidence: 90%
“…Results from this study showed a significant increase in both urinary NAG activity and NAG/Cr in diabetics compared with controls. These corroborate work done elsewhere [13, 22, 23]. This study also found significant elevations in both urinary AAP activity and AAP/Cr in the diabetics compared with controls.…”
Section: Discussionsupporting
confidence: 93%
“…One study suggests that the initial renal damage resulting in microalbuminuria is the loss of charge-dependent tubular protein reabsorption occurring prior to the damage of the glomerular charge barrier in diabetics [ 22 ] while another has shown in diabetic children that tubular proteinuria actually predates microalbuminuria [ 23 ]. We have previously demonstrated early tubular dysfunction in African diabetics using urinary NAG suggesting that tubular dysfunction may precede glomerular damage [ 24 ].…”
Section: Introductionmentioning
confidence: 99%